Mental Model Construction in MedlinePlus Information Searching Involves Changes and Developments in Cognition, Emotion, and Behaviour - DeRosa, Antonio (Evidence Based Library and Information Practice, 2013)
Objectives – To explore the construction of mental models as a dynamic process and how users understand a consumer health information system, MedlinePlus, during a search session. Design – Face-to-face interview. Setting – Large university. Subjects – A total of 38 undergraduate students participated in the study. All majoring in non-medical fields, such as art history, psychology, business, and communication studies. Methods – Participants were randomized into two groups: the simple task group and the complex task group. Simple task group members were asked to perform 12 simple tasks while the complex group members performed three more-involved tasks. Simple tasks were defined as succinct questions with finite answers while complex tasks were open-ended and required more cognitive activity and synthesizing on the part of the individual. Participants in both groups were then given four simple tasks and two complex tasks to perform. Data was derived by video recording search sessions with individuals and interview-like questions for the tasks performed. Participants were given a brief introduction to the search session design and sessions took place in a private lab. Since the aim of the study was to track participants’ mental modeling processes over time, coding of data was caught at three different times throughout the search sessions: T1 (MM1) after five minutes of free exploration, T2 (MM2) after the first search session, and T3 (MM3) after the second search session. Main Results – The author discusses the demographic specifics of the population participating in the study. Although participants were split into two groups, the results were combined to be more meaningful. Out of the 38 participants, 20 were female and 18 were male with ages ranging from 18 to 22. They had, on average, 10 years of computer experience and their average spatial ability score was 12.71. Also on average, they spent about 20 minutes completing the first search session and 12 minutes completing the second search session. The results show that participant-developed mental models of the MedlinePlus web space can be clustered into the following five theoretical components (this information is quantified in tables throughout the paper): system, content, information organization, interface, and procedural knowledge. Conclusion – The study allowed participants to articulate their mental models and representations while conducting predefined searches during private sessions using MedlinePlus. The study also illustrates how users’ mental models of a system developed during interactions with an online system, on a theoretical level. Little is actually known about how mental models are developed when users interact with an information system. The study serves to explore this arena and reveals that the mental model construction involves changes and developments in three parallel dimensions: cognition, emotion, and behaviour. Also, these dimensions are accompanied by three mental activities: assimilating new concepts, phasing out previously perceived concepts, and modifying existing concepts. The mental model construction process could be a useful tool to build user models and make better design decisions for information systems.